2019
DOI: 10.3389/fonc.2019.01378
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review of Low-Dose Rate (LDR) and High-Dose Rate (HDR) Brachytherapy Boost for High-Risk Prostate

Abstract: For patients with unfavorable or high-risk prostate cancer, dose escalated radiation therapy leads to improved progression free survival but attempts to deliver increased dose by external beam radiation therapy (EBRT) alone can be limited by late toxicities to nearby genitourinary and gastrointestinal organs at risk. Brachytherapy is a method to deliver dose escalation in conjunction with EBRT with a potentially improved late toxicity profile and improved prostate cancer related outcomes. At least three random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…HDR-BT treated more advanced cases than LDR-BT in our cohort. Several retrospective studies 14 16 and a few preliminary and premature prospective studies have reported benefits of HDR-BT 17 19 .…”
Section: Discussionmentioning
confidence: 99%
“…HDR-BT treated more advanced cases than LDR-BT in our cohort. Several retrospective studies 14 16 and a few preliminary and premature prospective studies have reported benefits of HDR-BT 17 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Advances in external RT with IMRT and image-guided radiation therapy have significantly reduced toxicities and improved outcomes. As a result, use of BT alone or as a boost has diminished over the last decades (21)(22). However, IMRT or stereotactic RT, although highly conformal, is not significantly better than BT in their ability to spare the surrounding previously irradiated tissues (4,19).…”
Section: Such Treatment Decisions Must Be Handled Only By Teamsmentioning
confidence: 99%
“…As a result, there is limited opportunity for the general oncologic society to have enough education about ReRT-BT. The American Brachytherapy Society has started a ''300 in 10'' initiative to increase the training of brachytherapists by assisting in the training of 30 oncologists per year over a 10-year period (21), which reflected the status of the present brachytherapy society. Enough experience could lead to more utilization of BT ReRT, as it is likely the responders who have high-level experience with BT would be more likely to perform BT.…”
Section: Such Treatment Decisions Must Be Handled Only By Teamsmentioning
confidence: 99%
“…Low-dose rate (LDR) and high-dose rate (HDR) BT have both been utilized in prostate cancer [11] . HDR-BT affords several practical, physical, and potential radiobiological advantages over LDR-BT [11] , [12] , [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Low-dose rate (LDR) and high-dose rate (HDR) BT have both been utilized in prostate cancer [11] . HDR-BT affords several practical, physical, and potential radiobiological advantages over LDR-BT [11] , [12] , [13] . While prospective trials have helped establish the benefit of HDR-BT boost and optimal dose/fractionation regimens [4] , [14] , [15] , [16] , there is no data to rationally inform optimal sequencing of the HDR-BT boost with regards to EBRT.…”
Section: Introductionmentioning
confidence: 99%